Modeling & Simulation of Fuel cell (Choi Model) based 3-Phase Voltage Source Inverter - Gaurav Sachdeva (Institute of Advanced Engineering and Science, 2011)
In the present work, performance of three phase voltage source inverter, while feeding different power factor loads, has been investigated. Fuel cells models namely Choi model are used in input side as a DC source while dynamic load have been used at the output side. Dynamic load used is induction motor (IM). Performance of IM has been investigated under various loading conditions. ANN based control strategy has been proposed to find the conduction angle of a Three Phase VSI and verified for IM load. Simulations have been performed using PSIM 7.0.5 and MATLAB 7.0.4.DOI : http://dx.doi.org/10.11591/ijpeds.v1i2.109